Prospects for Malaria Vaccines: Pre-Erythrocytic Stages, Blood Stages, and Transmission-Blocking Stages. (3rd October 2019) - Zheng, Jingtong; Pan, He; Gu, Yinuo; Zuo, Xu; Ran, Nan; Yuan, Yuze; Zhang, Chao; Wang, Fang
Abstract : Malaria is a disease of public health importance in many parts of the world. Currently, there is no effective way to eradicate malaria, so developing safe, efficient, and cost-effective vaccines against this disease remains an important goal. Current research on malaria vaccines is focused on developing vaccines against pre-erythrocytic stage parasites and blood-stage parasites or on developing a transmission-blocking vaccine. Here, we briefly describe the progress made towards a vaccine against Plasmodium falciparum, the most pathogenic of the malaria parasite species to infect humans.